(untitled) (Research, Society and Development, 2023)
This study aimed to evaluate the clinical performance of composite resin restorations performed by academics based on the criteria of marginal fit, surface texture, caries recurrence, retention and color. The research took place in two stages. The first was by collecting data from the medical records of patients at the Clinic-School of Dentistry at the Integrated Regional University of Alto Uruguai e das Missões. After collecting this information, the patients were contacted by telephone and invited to appear on the day and at the scheduled time, for the evaluation of the restorations (second stage). After 1.5 years, the restorations were evaluated using the modified USPHS method. Of the 32 selected patients, 96 restorations were evaluated. Class V types were the most prevalent (37.5%), followed by class III (32.3%) and class IV (30.2%). Most of the evaluated restorations were clinically satisfactory after 1.5 years of their execution, which showed that they were well executed. However, more studies are needed to evaluate the condition of these materials for a longer period of time.